Computational design principles for the discovery of bioactive dendrimers: [s]-triazines and other examples. (September 2013) - Simanek, Eric E; Enciso, Alan E; Pavan, Giovanni M
Abstract : Introduction: Chemistry yields dendrimers of many classes and compositions. Translating this synthetic success to bioactivity is significantly aided by the use of computational modeling and our knowledge of the three-dimensional shapes of these macromolecules. Areas covered: This review discusses the lessons learned during the investigations of [s]-triazine dendrimers. Specifically, the article focuses on the evolving role that computational models have taken in the exploration of these macromolecules. These lessons, furthermore, can be generalized across many dendrimer classes. Expert opinion: Computational models and the resulting structural data from molecular dynamics simulations provide insights into: shape, solvent penetration, shielding of biolabile linkers, and the density of hydrophobic patches. These models have evolved from artistic representations, through bases for rationalization, to hypothesis-generating tools that drive synthesis. With further advances expected in both software and hardware the answer to the question, 'What does a specific dendrimer look like in solution?' is becoming increasingly clear. Moreover, the authors believe that answer to this question lies at the heart of the design of bioactive dendrimers.